Excellent rheological performance and impact toughness of cellulose nanofibers/PLA/ionomer composite. Issue 46 (1st June 2017) - Li, Jingjing; Li, Jian; Feng, Dejun; Zhao, Jingfeng; Sun, Jingrong; Li, Dagang
Abstract : Ionomer can be used as an ideal compatibilizer to improve simultaneously both the flowability and the mechanical properties of cellulose nanofibers/PLA composite. Abstract : Cellulose nanofibers (CNFs) with high aspect ratio were used to reinforce polylactic acid (PLA) by extrusion. Surlyn ionomer was adopted to improve the interfacial adhesion and impact toughness of the CNFs/PLA composite. To overcome the aggregation of CNFs, a water preblending process was carried out before the extrusion. The rheological results showed the ionomer can decrease the viscosity of the CNFs/PLA composite and improve the flowability due to the lubrication of the ionomer. The bending strength (MOR) and bending modulus (MOE) of the composite with ionomer were much higher than those of a composite with maleic anhydride grafted polyethylene (MAPE). In addition, the CNFs/PLA/ionomer composite showed extremely high impact toughness, which was up to 34.2 J m −1 when the loading of CNFs was 30 wt%, increasing by 302.3% as compared to neat PLA. FE-SEM images demonstrated the homogenous dispersion of CNFs in PLA by using the water preblending method.